Evaluación ecológica rápida de la vegetación arbórea del bosque siempreverde montano del sur de la Cordillera Oriental de los Andes, sector Imbana, Zamora Chinchipe - Castillo Acaro, Estefanía Nathaly (2021)
Tropical montane forests are among the most diverse ecosystems in the world, they are a hot spot of biodiversity, and they also play a key role in the supply of ecosystem goods and services. However, they are poorly studied and there is little knowledge about tropical Andean montane forests. The objetive of this study was to determine the floristic composition, structure and endemism of the evergreen montane forest of the south, Imbana sector, Zamora Chinchipe. Six transects of 20 m x 50 m were installed, trees were sampled with DAP ≥ 10 cm; the natural regeneration of tree species was evaluated on nested plots of 4 m2 for the study of saplings, 25 m2 for low latizals and 100 m2 for high latizals. The diameter, total height and commercial height were measured from each tree. The floristic composition, structural parameters of vegetation, dasometric parameters, specific diversity and endemism were determined. The specific diversity was obtained through the calculation of the Shannon (H) and Simpson (σ) indexes. The floristic composition of the evergreen montane forest consists of 94 species of 53 genera and 35 families, with a total of 424 registered individuals. The most ecologically important species are Graffenrieda emarginata, Alchornea lojaensis, Cyathea sp. and Drimys granadensis. There were 500 natural regeneration individuals from 98 species, 53 genera and 35 families. The greatest amount of natural regeneration was concentrated in the low latizal category with 210 ind/ha, followed by high latizal with 157 ind/ha and sapling with 133 ind/ha. A total volume of 138,48 m3/ha, commercial volume of 79,87 m3 /ha and basal area of 17,85 m2/ha is reported. The structure of the forest presented an inverted "J" distribution, where the largest number of individuals concentrated between classes I, II and III with 364 individuals representing 85,85 % of the total recorded, indicating that the forest is mostly composed of young individuals. Values obtained with the diversity indices of Shannon (3,96) and Simpson (0,97) indicated that the forest has a high diversity; in terms of endemism, six endemic species were recorded: Graffenrieda harlingii, Symplocos fuscata, Persea cf. bullata, Meriania rigida, Geissanthus vanderwerffii and Eugenia valvata, which points to the importance of the conservation and proper management of the floristic richness of this forest. Keywords: montane forest, floristic composition, diversity, natural regeneration, endemism